PENGARUH CORE STABILITY EXERCISE TERHADAP PENURUNAN NYERI DAN PENINGKATAN KEMAMPUAN FUNGSIONAL LOW BACK PAIN MYOGENIC PADA LANJUT USIA - Wahyuni, Wahyuni; Ana Sayida, Alissa (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Myogenic Low Back Pain (LBP) is a musculoskeletal problem that often occurs especially in the elderly, caused by muscle and soft tissue disorders in the lower lumbar region. Core Stability Exercise (CSE) is an exercise method that aims to strengthen core muscles, improve body stability, and reduce mechanical loads on the spine. Aims to determine the effect of CSE on reducing pain and functional improvement in myogenic LBP, especially in elderly Methods: This study applied a quasi-experimental design with a two-group pretest-posttest design approach. Using purposive sampling technique, involving 20 elderly with myogenic low back pain (LBP). Divided into two groups: an intervention group that underwent Core Stability Exercise for 4 weeks with a frequency of 3x/week, and a control group that only received education at the end of the study. Pain intensity was measured using the Numerical Rating Scale (NRS), while functional ability was assessed using the Roland-Morris Disability Questionnaire (RMDQ). Data analysis was performed using Wilcoxon test and Mann-Whitney U Test, with a significance level of p<0.05. Results: The study showed that in the intervention group, there was a significant decrease in pain with a value of p=0.014 for silent pain, p=0.003 for pressure pain, and p=0.002 for motion pain. Functional ability also increased significantly with a value of p=0.004. Meanwhile, in the control group, there were no significant changes in either pain level (p>0.05) or functional ability (p=0.102>0.05). Conclusion: Core Stability Exercise is proven to play a role in reducing pain and improving physical function in the elderly who experience myogenic Low Back Pain (LBP). Keywords: Myogenic Low Back Pain, Core Stability Exercise, Elderly, Pain and Functional Ability